2007
DOI: 10.1007/s10350-006-0787-8
|View full text |Cite
|
Sign up to set email alerts
|

Acute Diverticulitis in Very Young Patients: A Frequent Surgical Management

Abstract: Diverticulitis in patients younger than aged 40 years seems to have a particularly aggressive and fulminant course and requires early surgical procedures for complications (associated abscess, colonic perforation) in 40 percent of cases. The use of "major procedure" (i.e., stoma) is more frequent in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
2
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 20 publications
(23 reference statements)
1
29
2
5
Order By: Relevance
“…It has been reported that younger patients are more prone to recurrent disease and more frequently require surgery for complicated diverticulitis, supporting the recommendation of elective surgery after their first episode of uncomplicated diverticulitis [21,22,23,24,25]. In a recent study, no differences in the rate of successful conservative treatment were observed between patients at the first episode and those with recurrence with regard to age, suggesting that age is not a predictive factor of poor outcome [26].…”
Section: Risk Factorsmentioning
confidence: 99%
“…It has been reported that younger patients are more prone to recurrent disease and more frequently require surgery for complicated diverticulitis, supporting the recommendation of elective surgery after their first episode of uncomplicated diverticulitis [21,22,23,24,25]. In a recent study, no differences in the rate of successful conservative treatment were observed between patients at the first episode and those with recurrence with regard to age, suggesting that age is not a predictive factor of poor outcome [26].…”
Section: Risk Factorsmentioning
confidence: 99%
“…[1][2][3][4] Meanwhile, the severity and natural history of diverticulitis in the young population has been questioned. 5 Some authors continue to maintain that diverticulitis in the young takes an aggressive course, with a higher risk of complications and need for emergency surgery, 6,7 whereas others suggest the course of diverticulitis does not differ in young patients compared with older patients. 8 -16 Therefore, important questions remain.…”
mentioning
confidence: 99%
“…Ähnliches gilt sicherlich für immunkompromittierte Patienten [37]. Jüngere Patienten mögen zwar ein erhöhtes Risiko für eine Komplikation im Rahmen der Erstmanifestation haben [38], nicht aber ein erhöhtes Risiko für komplizierte Divertikulitisschübe im Verlauf [39]. Somit ergibt sich die Indikation in erster Linie aus dem möglichen langen Verlauf mit der Möglichkeit, über die Jahre viele Schübe zu erleiden.…”
Section: Disclosure Statementunclassified